1984
DOI: 10.1002/jso.2930270305
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of the liver in the management of metastatic carcinoid tumors

Abstract: Eight patients with metastatic carcinoid tumors and the carcinoid syndrome were treated with gelatin foam embolization of the hepatic arterial tree. The aims were to reduce the tumor mass in the liver and to eliminate the carcinoid syndrome. The effects of the treatment were judged from arteriograms, CT scans, and the levels of serotonin in blood and 5-HIAA in urine, as well as from the clinical symptoms. The mean follow-up time was 12.5 months. In all patients the liver tumor mass was reduced after embolizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…These authors reported persistent arterial occlusion on angiograms performed 6 weeks after TAE but did not evaluate other outcomes [ 25 ]. Further studies reported hepatic artery embolization with absorbable gelatin powder (i.e., slurry) with similar results [ 8 , 26 , 27 ]. However, gelatin powder is no longer used because it is associated with a high risk of complication due to non-targeted embolization [ 28 ].…”
Section: Transarterial Embolization and Transarterial Chemoembolizmentioning
confidence: 71%
See 2 more Smart Citations
“…These authors reported persistent arterial occlusion on angiograms performed 6 weeks after TAE but did not evaluate other outcomes [ 25 ]. Further studies reported hepatic artery embolization with absorbable gelatin powder (i.e., slurry) with similar results [ 8 , 26 , 27 ]. However, gelatin powder is no longer used because it is associated with a high risk of complication due to non-targeted embolization [ 28 ].…”
Section: Transarterial Embolization and Transarterial Chemoembolizmentioning
confidence: 71%
“…NELMs of the caudate lobe (i.e., segment I) have a lower radiological response to transarterial therapy than those in other segmental locations (12% vs. 82%, respectively) with consequent lower OS (46 vs. 87 months; p = 0.031) [ 56 ]. When several sessions of TAE or TACE are performed, responses after following sessions are similar to the first one for clinical improvement and biological response [ 26 , 62 ]. However, when NELMS favorably respond to the first session, a repeat session improves the OS [ 26 , 62 ].…”
Section: Transarterial Embolization and Transarterial Chemoembolizmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach to treatment of liver metastases has become increasingly aggressive and the regimens at present comprise hepatic liver dearterialization, embolization, and chemotherapy. These treatments are usually effective, but expensive and not without complications [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with small-intestine NETs or NETs of unknown primary with a urinary 5-HIAA doubling time < 434 days had a significantly higher disease-specific mortality compared to those with longer doubling times [ 83 ]. Several studies have described reduction of 5-HIAA levels after transarterial liver-directed therapy [ 84 , 85 , 86 , 87 ]. Carrasco et al’s study evaluating hepatic artery embolization in patients with malignant carcinoid syndrome found reduction in urinary 5-HIAA levels in all patients who had objective imaging and clinical response [ 86 ].…”
Section: Prognostic Biomarkers and Genesmentioning
confidence: 99%